Urban Screen pada Ruang Publik: Media Interaksi Kreatif dalam Meningkatkan Makna Tempat - Litta Primasari; Setiawan Sabana (Wimba : Jurnal Komunikasi Visual, 2010)
Urban screen is a new media screen that performs on the public space. Its existence isnot only enriches the visual landscape of public space, it also indirectly creating public participation both passive and active. If properly created, urban screens can produce relational space that useful to increase the meaning of place. The emergence of relation between physical space and virtual space, material and immaterial, dynamic and static, and between public and private interests will produce the augmented place. The Augmented place will continually create a new different place from we have known. The existences of new media screen may inspire the public to interact among people and people with the place and in the end creates engagement with the place. This paper contributes to inspire the urban planners to increase the meaning of the place in the city of space which have decreased in space quality and provide motivation for the artists to build interaction between art work and public sphere. This paper will focuses on the emergence of relational space in the form of public response to the urban screen.